2012
DOI: 10.1172/jci63455
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-122 plays a critical role in liver homeostasis and hepatocarcinogenesis

Abstract: MicroRNA-122 (miR-122), which accounts for 70% of the liver's total miRNAs, plays a pivotal role in the liver. However, its intrinsic physiological roles remain largely undetermined. We demonstrated that mice lacking the gene encoding miR-122a (Mir122a) are viable but develop temporally controlled steatohepatitis, fibrosis, and hepatocellular carcinoma (HCC). These mice exhibited a striking disparity in HCC incidence based on sex, with a male-to-female ratio of 3.9:1, which recapitulates the disease incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
730
4
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(761 citation statements)
references
References 63 publications
(75 reference statements)
20
730
4
7
Order By: Relevance
“…Recent studies found that miR-122 is frequently suppressed in hepatocellular carcinomas (Bai et al, 2009;Tsai et al, 2012) and breast cancer specimens (Wang et al, 2012). Overexpression of miR-122 could suppress proliferation and induce apoptosis and cell cycle arrest in cancer cells through reducing the expression of Bcl-W, CCNG1 (Ma et al, 2010), IGF1R/PI3K/Akt (Wang et al, 2012) and Wnt/beta-catenin signal pathways (Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that miR-122 is frequently suppressed in hepatocellular carcinomas (Bai et al, 2009;Tsai et al, 2012) and breast cancer specimens (Wang et al, 2012). Overexpression of miR-122 could suppress proliferation and induce apoptosis and cell cycle arrest in cancer cells through reducing the expression of Bcl-W, CCNG1 (Ma et al, 2010), IGF1R/PI3K/Akt (Wang et al, 2012) and Wnt/beta-catenin signal pathways (Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2013), Fan et al (2011) showed that low miR-122 levels stimulated HBV replication and overexpression of viral antigen with subsequent cellular damage, overgrowth and hepatocellular fibrosis. Indeed, low levels of miR-122 stimulated Klf6, a fibrosis activator (Tsai et al, 2012). Circulating levels of miR-122 are elevated with good diagnostic performance.…”
Section: Mir-122mentioning
confidence: 99%
“…40,44,45 Serum/plasma levels of miR-122 correlate with hepatic necro-inflammation, liver damage, cell death and increased aminotransferase levels in acute and chronic liver diseases. 44,[46][47][48][49] Interestingly, hepatic and circulating miR-122 levels do not correlate in NAFLD 14,39,[50][51][52][53][54][55] or viral hepatitis 41,47,49,56 although both have been statistically associated with various measures of disease severity in these studies. Together these studies show that miR-122 may play a role in most liver diseases.…”
Section: Microrna-122mentioning
confidence: 62%
“…12,14 The targeted deletion of miR-122a in mice results in NASH, fibrosis and HCC. 54 In miR profile analysis of high fat fed rat liver, 14 miRs were up-regulated and six were down-regulated, that might represent a distinctive molecular signature in the transition of steatosis to steatohepatitis. 53 MiR-34a and miR146b were shown to be significantly over-expressed (99% and 80%, respectively) in human NASH.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 97%